ESTIMATION OF INSPIRATION AND EXPIRATION TIME BY USING FUZZY CONTROL WITH RESPECT TO LUNG'S DYNAMICS - Guler, Hasan; Ata, Fikret (Ieee, 2010)
In this study, estimation of inspiration and expiration time in positive pressure ventilator, which is used in intensive care units and implements patient's artificial respiratory system that has been disturbed is performed with fuzzy logic controller. The goal of this system is to reduce workload of anaesthetist. Since he/she has many patients in intensive care units so he has no so much time each patients. Fuzzy logic controller determines time of inspiration and expiration. By estimating inspiration and expiration time, lung's dynamics which are resistance and compliance are considered. Performed system is run in the pressure control ventilation (PCV) which is one of the most used modes among other ventilation modes.
5th International Conference on Soft Computing, Computing with Words and Perceptions in System Analysis, Decision and Control -- SEP 02-04, 2009 -- Famagusta, CYPRUS